The level of job satisfaction and its relationship to the quality of life of school principals in the Karak Directorate of Education from their point of view - Al-Takhaineh, Halla Jebril Abniya (Journal of Educational and Psychological Sciences, 2022)
The study aimed to identify the level of job satisfaction and its relationship to the quality of life of school principals in the Karak Directorate of Education from their point of view in the Hashemite Kingdom of Jordan. It was distributed to an intentional sample of (80) male and female managers. The results of the study concluded that the principals’ job satisfaction axis scored an average (2.89 out of 5), i.e. at a (medium) degree, while the managers’ quality of life axis got an average (2.82), i.e. a (medium) degree, and it was also found that there is a positive relationship between job satisfaction and quality of life. where the total correlation coefficient between them was (0.90), which means a (very strong) correlation. There are no statistically significant differences in job satisfaction and quality of life according to the gender variable. Based on the results, the researcher made a number of recommendations to raise the level of job satisfaction and quality of life for school principals in the Karak Education Directorate and throughout the Kingdom of Jordan, in addition to suggestions for future studies on the subject.
Keywords: job satisfaction; quality of life; public school principals; Karak Governorate; Kingdom of Jordan